Gambaran Pengetahuan dan Tindakan Pencegahan Penyakit Malaria di Desa Tateli I Jaga I Kecamatan Mandolang Kabupaten Minahasa - Karundeng, Regina J.; Rombot, Dina V.; Sapulete, Margareth R. (UNIVERSITAS SAM RATULANGI, 2013)
Malaria is one of the disease that gives quite high morbidity and mortality in this wolrd. Malaria is a disease with the 3rd amount of death. In Indonesia, Malaria is still main healthy problem because it influences rate of illness in baby, give birth mother and caused extraordinary event ( KejadianLuarBiasa – KLB ). Based on RISKESDA 2009/2010 Ma-laria case in Sulawesi Utara is 61, 7 %. The goal of this research is to figure out the knowledge and preventing action has been done by Tateli citizen over Malaria disease. This research is a descriptive and survey method. The sampling of this research has been taken at Jaga I, that is one of the area where the mosquito grow. The result of this research shows that the knowledge of Tateli I Jaga I citizen is good, shown by caused and signed of Malaria that has been known for 90 % and the preventing action over Malaria disease is not really good, because we can find 76 % that didn’t use wire, and 89 % didn’t use mosquito net in their house.